Organic Bioelectronics: Bridging the Signaling Gap between Biology and Technology - Simon, Daniel T; Gabrielsson, Erik O; Tybrandt, Klas; Berggren, Magnus (Chemical reviews, 2016)
The electronics surrounding us in our daily lives rely almost exclusively on electrons as the dominant charge carrier. In stark contrast, biological systems rarely use electrons but rather use ions and molecules of varying size. Due to the unique combination of both electronic and ionic/molecular conductivity in conducting and semiconducting organic polymers and small molecules, these materials have emerged in recent decades as excellent tools for translating signals between these two realms and, therefore, providing a means to effectively interface biology with conventional electronics-thus, the field of organic bioelectronics. Today, organic bioelectronics defines a generic platform with unprecedented biological recording and regulation tools and is maturing toward applications ranging from life sciences to the clinic. In this Review, we introduce the field, from its early breakthroughs to its current results and future challenges.